Przez Ty człowiek staje się Ja. Coaching i filozofia dialogu – konstruktywne spotkanie - Teusz , Grażyna (Studia Edukacyjne, 2017)
The article discusses selected aspects of the philosophy of dialog, and then makes relations between them and the theory and practice of coaching. The platform which significantly bridges the two approaches is the perspective of encounter and the dialogical relation, which come into play in the interpersonal I and You relation (coach – client) and the resultant experience, conditions and consequences. Empathy is one of the possible efficient tools of dialog. It is a criterion for a genuine encounter that is one of the assumptions of the philosophy dialog.